PENGABDIAN KEPADA MASYARAKAT MELALUI WEBINAR PENGENALAN PEMBELAJARAN MENDALAM UNTUK MENINGKATKAN KUALITAS PENDIDIKAN - Alimin Alwi; Ahmad Jamalong; Bakhtiar; Bastiana; Mustari (Lembaga Penelitian, Publikasi, & Pengabdian kepada Masyarakat, Universitas Satya Negara Indonesia (LP3M-USNI), 2026)
This community service activity aims to increase educators' and students' understanding of the concept of deep learning as a strategic approach in efforts to improve the quality of education. Deep learning is considered important because it emphasizes conceptual understanding, the development of critical and reflective thinking skills, and the relevance of learning to real-life contexts. This activity was conducted in the form of an online seminar via the Zoom Meeting platform on November 26, 2025. There were 178 participants consisting of students, educators, and the general public from various universities and educational institutions in South Sulawesi and its surroundings. The methods used in this activity included the delivery of material by speakers who are competent in the field of education, interactive discussions between the speakers and participants, as well as reflections and feedback from participants on the material presented. The seminar material focused on the basic concepts of deep learning, its urgency in responding to current educational challenges, and its differences from conventional learning, which is still oriented towards memorization. The interactive discussion provided a space for participants to ask questions, share experiences, and reflect on the learning practices that have been implemented so far. The results of the activity showed an increase in participants' conceptual understanding of deep learning and an increased awareness of the importance of critical, reflective, contextual, and meaningful learning. The enthusiasm and active participation of the participants during the activity were indicators of the success of this community service program. This activity is expected to make a real contribution to strengthening the capacity of educators and students and encouraging their readiness to implement deep learning sustainably in the educational environment.